The self-management strategies for diabetic patients under treatment in the primary health care facilities of the Sekhukhune District of the Elias Motsoaledi Municipality in the Limpopo Province, South Africa - Makofane, Pheladi Doreen (My University, 2019)
Background: Non-attendance of diabetic patients at primary health care facilities for scheduled appointments has been identified as one of the most pressing issues in chronic illness, including diabetes mellitus, management and results into uncontrolled illnesses. Diabetes mellitus has an increased mortality and morbidity rate, thus has been identified as the second most frequent killer disease in South Africa. Aim of the study: The purpose of the study is to determine self-management strategies to maintain a healthy life for diabetic patients under treatment in primary health care facilities in the Sekhukhune District. Methods: A qualitative, phenomenological, explorative and descriptive study design was conducted in 5 clinics of the Sekhukhune District in the Elias Motswaledi Municipality in Limpopo Province. Data were collected through one-to-one interviews using semi-structured guide. An non-probability purposive sampling method was used to select participants until data saturation was reached. Data were analysed using Tech’s coding qualitative data analysis approach. Results: The findings of this research reveal that diabetic patients know the importance of adherence to diet. However, they also elaborated on the challenges they face, like inability to afford proper diet and their stress levels. They are aware of predisposing factors and recommend support structures like food parcels as well as adhering to the prescribed treatment. Conclusion and recommendations: Diabetic patients lack self-management strategies to maintain their quality of life when diagnosed with diabetes. Furthermore, the study concludes that diabetics lack encouragement and empowerment from health care workers and their families. The study recommends that diabetic patients adhere to a prescribed diet and treatment and that they could be offered food parcels and taught how to avoid factors that could trigger stress. Additionally, it is recommended that support structures be developed to assist diabetic patients about self-management strategies that they could use in order to maintain a good quality of v life. It is also recommended that the Department of Health employ Home-Based Carers in the facilities to assist diabetic patients with their day-to-day care.
Thesis (M. A. (Nursing Science)) -- University of Limpopo, 2019
Keywords: Diabetes mellitus; Self-management; Strategies; Lifestyle modification; Medication; Diabetics -- South Africa -- Limpopo; Diabetics -- Care -- South Africa -- Limpopo; Diabetes -- Treatment -- South Africa -- Limpopo